CHARACTERISTICS OF REFLECTIVENESS IN ADOLESCENT PERIOD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article presents an analysis of thoughts on the psychological factors of the formation of reflexivity during adolescence. In particular, the psychological aspects of the manifestation of such processes as self-awareness, personal reflection, self-control, and self-control in thinking are revealed in the adolescent personality. Also, age-related development characteristics of situational, personal, cooperative, communicative (social-psychological), cognitive or intellectual, situational reflection, retrospective, prospective reflections during adolescence are explained.